Comparison of 11C-Choline and 11C-Methionine PET/CT in Multiple Myeloma. (August 2019) - Lapa, Constantin; Kircher, Malte; Da Via, Matteo; Schreder, Martin; Rasche, Leo; Kortüm, K. Martin; Einsele, Hermann; Buck, Andreas K.; Hänscheid, Heribert; Samnick, Samuel
Abstract : Purpose: PET/CT with both 11 C-choline and 11 C-methionine has recently been reported to offer advantages over 18 F-FDG for imaging in multiple myeloma (MM). The aim of this study was to directly compare the diagnostic performance of both non-FDG radiotracers in MM patients. Methods: Nineteen patients with a history of MM (n = 18) or solitary bone plasmacytoma (n = 1) underwent both 11 C-choline and 11 C-methionine PET/CT for diagnostic imaging. In this retrospective analysis, scans were compared on a patient and on a lesion basis. In 12 patients, respective tracer uptake in the iliac crest was correlated with the extent of malignant bone marrow plasma cell infiltration. Results: 11 C-methionine detected more intramedullary MM lesions in 8 (42.1%) of 19 patients. In the remainder (11/19 [57.9%]), both 11 C-choline and 11 C-methionine provided equal results. 11 C-methionine demonstrated higher lesion-to-muscle ratios ( P = 0.0001). In the 12 patients in whom a recent bone marrow biopsy was available, SUVmean as well as SUVmax correlated significantly with the degree of malignant plasma cell infiltration for both 11 C-methionine (SUVmean: r = 0.85, P < 0.001; SUVmax: r = 0.82, P = 0.001) and 11 C-choline (SUVmean: r = 0.72, P < 0.008; SUVmax: r = 0.73; P = 0.006). Conclusions: Our data suggest that 11 C-methionine PET/CT might be more sensitive than 11 C-choline PET/CT for the detection of active MM lesions. Abstract : Supplemental digital content is available in the text.